The Effect of Various Factors on the Emulsifying Stability of Gums- a Comparative Study - A. Omer, Elgaili.; E. Abdulaziz, M.; E. Osman, M. (Gezira Journal of Engineering and Applied Sciences, 2009)
Emulsifying stability of Acacia polyacantha gum has been studied  in  comparison  with  other  Acacia  species, such  as A. senegal and A seyal.It could be concluded that addition of protein improved  the  emulsifying  stability of the gum. Increasing  of concentration  (0.05% to 0.4%) increases the emulsifying stability of all the three gums. Blend of A. polyacantha and A. seyal that contain  25%  A.  polyacantha  and 75% A. seyal was found to possess superior properties (1.04) compared to parent polyacantha gum (0.97). It has been demonstrated that the high molecular weight protein rich fraction of the gum is preferentially adsorbed to the oil phase during emulsification process. The emulsifying stability  of divalent  ions  was  high for calcium polyacanthate, calcium    senegalate   and   calcium   seyalate,  while  that  of monovalent  ions  was  low  for sodium polyacanthate, sodium senegalate  and sodium  seyalate. It was clear that with increase in PH values up to (9), the emulsifying stability decreases (0.95), increasing  the  time  of  stirring (l — 5min),  it  increased  the emulsifying   stability   (0.93 to 1.03). The  rise  in  temperature (450C- 850C) (0.99 0.76) resulted in declining the emulsifying stability of the gum.